Des athlètes trans aux Jeux olympiques ? Histoire d’une panique de genre dans la presse française (1935-2022) - Félix Pavlenko; Karl Ponthieux Stern (Genre & Histoire)
Trans athletes’ participation in the Olympic Games may seem recent in the media and social landscape. Contrary to this view, this article proposes to delve into the erased history of a century of trans presence at the Olympics. Our analysis rests on a corpus of 231 articles from the French mainstream, sports and LGBTI press, published between 1935 and 2022. The results demonstrate the presence of a gender panic, periodized in four key periods: 1) the beginnings of a gender panic (1935-2002), 2) amplification of an essentialist perspective (2003-2015), 3) gendered differentiation of the contemporary gender panic (2015-2020), 4) media explosion since the Tokyo Games (2021-2022). This research thus contributes to understanding the role of cissexism in maintaining the gendered order within Olympism.